Handshake stewardship reduces carbapenem prescription in a pediatric critical care setting. Issue 1 (1st August 2022) - Kit‐Anan, Waratchaya; Boonsathorn, Sophida; Anantasit, Nattachai; Techasaensiri, Chonnamet; Chaisavaneeyakorn, Sujittra; Apiwattanakul, Nopporn
Abstract: Background: Intensive care unit (ICU) settings typically have a high‐volume prescription of carbapenems. Antimicrobial stewardship programs (ASPs) aim to promote appropriate antibiotic use. Handshake stewardship (HS) is adapted from ASPs but focuses on direct feedback to physicians who prescribed antibiotics regarding the appropriateness of antibiotic prescription. This study aimed to evaluate the impact and acceptability of HS on carbapenem consumption in pediatric critical care settings. Methods: This study was conducted over 18 months spanning pre‐and post‐implementation of HS. Carbapenem prescriptions were automatically discontinued during the pre‐implementation period after 72 h if no indications existed. During the post‐implementation, HS was performed by direct feedback to ICU physicians regarding the appropriateness of carbapenem prescriptions within 24 h. The primary outcome was the carbapenem consumption rate, defined as days of therapy (DOT)/1, 000 patient‐ICU days. Secondary outcomes were the acceptability of HS, length of critical care stay (LOCS), 30‐day infection‐related mortality rate, and the rate of carbapenem‐resistant Enterobacteriaceae (CRE). Results: There were 212 carbapenem prescriptions (163 patients) and 174 carbapenem prescriptions (110 patients) in the pre‐and post‐implementation periods, respectively. Carbapenem consumption decreased significantly from 667 to 369 DOT/1, 000 patient‐ICU days, with a median difference of 292 DOT/1, 000 patient‐ICU days ( P < 0.001; 95% confidence interval: 175–408) after HS implementation. The acceptability of the HS was 95.4%. The LOCS, 30‐day infection‐related mortality, and CRE rate were not significantly different between pre‐and post‐implementation periods. Conclusions: Handshake stewardship significantly reduced carbapenem prescription in critically ill pediatric patients without negatively affecting patient outcomes.